THE NORM OF PHYSICAL ACTIVITY OF SCHOOLCHILDREN DURING THE DAY (Scientific journal of the Fergana State University, 2024)
The article highlights the widespread implementation of a healthy lifestyle and the further development of mass sports by following the norms of schoolchildren's activity during the day. Also, due to the rate of movement activity of schoolchildren, the lack of physical load on the body, fat and connective tissue cover part of the heart muscle fibers, reducing the ability of the muscles to contract, reducing the elasticity of the walls of the main blood vessels in the cardiovascular system. , the consequences of which are the reasons for the increase in arterial pressure.